Framework for industry engagement and quality principles for industry-provided medical education in Europe. Issue 1 (1st January 2017) - Allen, Tamara; Donde, Nina; Hofstädter-Thalmann, Eva; Keijser, Sandra; Moy, Veronique; Murama, Jean-Jacques; Kellner, Thomas
ABSTRACT: Lifelong learning through continuing professional development (CPD) and medical education is critical for healthcare professionals to stay abreast of knowledge and skills and provide an optimal standard of care to patients. In Europe, CPD and medical education are fragmented as there are numerous models, providers and national regulations and a lack of harmonisation of qualitative criteria. There is continued debate on the appropriate role of pharmaceutical companies in the context of medical education. Accrediting bodies such as European Accreditation Council for Continuing Medical Education do not permit active involvement of the pharmaceutical industry due to concerns around conflicts of interest and potential for bias. However, many examples of active collaboration between pharmaceutical companies and medical societies and scientific experts exist, demonstrating high integrity, clear roles and responsibilities, and fair and balanced content. Medical education experts from 16 pharmaceutical companies met to develop a set of quality principles similar to standards that have been established for clinical trials and in alignment with existing principles of accrediting bodies. This paper outlines their proposal for a framework to improve and harmonise medical education quality standards in Europe, and is also an invitation for all stakeholders to join a discussion on this integrative model.